The Impact of Innovative Work Environment Quality on the Performance of Small Enterprises (A Field Study in Latakia Governorate) - عيسى, يارا (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The research aims mainly to shed light on the concept of innovative work environment quality, and the concept of small projects performance and its dimensions represented in (profitability, market share, growth in the number of employees), and to show the impact of innovative work environment quality on the performance of small and medium enterprises. The researcher relied on the descriptive analytical approach. In the theoretical framework, the researcher addressed the concept of the work environment and its components, and also addressed the concept of innovative work environment, and the criteria for measuring the quality of the innovative work environment. The researcher also addressed the concept of performance, the concept of small projects and their importance. In the practical framework, the researcher relied on the questionnaire as a tool for collecting data, and the (SPSS) program was relied upon to analyze the data, test the hypotheses and reach the research results. The research reached several results, the most important of which is the presence of a moderate moral impact of innovative work environment quality on the performance of small projects in the study area.